EMBEDDING HEALTH RESEARCH FINDINGS INTO POLICY MAKING: POLICYMAKERS AND ACADEMICIANS PERSPECTIVE, PALESTINE, 2013 - Aljeesh, Yousef Ibrahim; Al-Khaldi, Mohammed Shoukri (European Scientific Journal, ESJ, 2014)
Background: There is growing interest in understanding how to effectively bridge the gap between the production of knowledge and it’s embedding in health decision-making. Health research s upports health systems in the delivery of better, fairer and more equitable health care to people. It does so by identifying challenges and providing best solutions in emerging and embedding theses research findings into policies in order to improved approaches to public health. So, the research findings are extremely important to inform policy and decision-making in health to tackle threats and diseases, to address priorities and focus on the most important health issues. Ultimately, the concept of evidence-based practice or policy-based evidence aims to improve health system performance and attain sustainable development. However, policy-makers, particularly in Palestine may not recognize the contribution which research can make. There is a huge gap between the scope of research and the scope of policy-making. The stereotype of the researcher in ivory tower still prevails. In fact, health officials and policy-makers may be doing research without knowing it, and researches that conducted by universities are not adopt and not invest of it. This study aims to understand and assess the research findings embbeddedness into decisions and policies in Palestine from policymakers and academicians perspective. Design and methodology: The study design was a qualitative approach by using indepth interviews for gathering and elaborating data about the phenomenon. The study participants included seven in-depth interviews; three of them with graduate faculty’ members at the universities, two policy makers from Ministry of Health (MOH), one expert from Non- Governmental Organizations (NGOs) and International NGOs (INGOs), and the last one parliamentary from Palestinian Legislative Council (PLC) who engage in this field. Findings: through the thematic analysis, the study main findings revealed that the degree of embeddedness is remarkably faint across the MOH in particular and moderately respectable in the academic, NGO, and INGOs institution, the overall impression about evidence-based practice in the health sector is very weak due to many obstacles that were identified. Most importantly, there is a significant weakness in research culture in the health institutions as well as mal-practice and poor experience, and no clear national health research priorities, strategy. There are various obstacles hindering evidence embeddedness into policies which are: systems issues such centralization and lack of incentives and capacity building programs as staff and fund insufficiency, poor information infrastructure and logistical and technological capacities also absence of knowledge transfer "dissemination". Moreover, communication, networking, and coordination across institutions and researchers and policy makers were fragile. Also, the majority stated that the evidence-based practice is not appropriately use and mostly personally-driven and actually not institutionalized, since the researchers’ role is mainly minor as well as the relationships among institutions is not wellestablished. Recommendations: the researcher emphasizes on the necessity of taking the research evidences into consideration. Urge MOH, Universities, NGOs, INGOs, and institutes, and to its members to build effective relationship to play a complementarily role and work as a team to find solutions to research-relevant policy obstacles and to enforce the research utilization and institutionalization by active communication and coordination. Also, allocate sufficient financing and logistics and qualified human resources through capacity building, presence of supportive culture and system such leadership, incentives, find research units. Also, more concern in applied research quality and credibility to use appropriately. The necessity for embracing agreed research-policy and priorities integration strategy to support the research system primarily and to empower the Palestinian health care system based on national health goals and needs to attain sustainable health development.